Update on the management of diabetes during Ramadan fast for healthcare practitioners - Rathor, Mohammad Yousuf; Fauzi, Abdul Rani; Omar, Ahmad Marzuki (Faculty of Medicine, International Islamic University Malaysia, 2014)
Fasting during the month of Ramadan is one of the five pillars of Islam, a recurring annual ritual, which is passionately practiced by most Muslims across the world. It is obligatory on every healthy Muslim; however, the Qur’an and Islamic teachings specifically exempt people with acute or chronic illnesses from this duty, especially if it might have harmful consequences. Muslims with diabetes are exempted from fasting, but many of them still fast during Ramadan, for their personal convictions as revealed by EPIDIAR study which showed that 43% of patients with type 1 diabetes and 79% with type 2 diabetes fasted during Ramadan. Muslims constitute about a quarter of the world’s population who are spread all over the globe. It is inevitable that health care issues peculiar to them will be encountered worldwide and health care providers will have to counsel them regarding medications and whether it is safe to undertake the fast. This paper is an update on the management of Ramadan fasting based on current evidence from published literature and expert opinions